SELECTING ENGLISH TEXTBOOK FOR VOCATIONAL SCHOOL STUDENTS USING CUNNINGSWORTHS MODEL - Rubiasih, Hasti . (Majalah Transformatika, 2010)
Textbook plays a very important role in supporting the process of learning-teaching English because it serves as sources of learningÂ teaching activities and materials. As most teachers are not capable of producing good textbooks, they tend to rely on those available Â on market. In selecting them, Cunnings worth offers brief and applicable guidelines which cover the notion of needs, uses, supports for learning and teaching processes. Finally, teachers need to make some modification to the selected textbooks to best suit to support the success of learning-teaching process. Key words: curriculum, textbook, needs analysis, competence.